PEMANFAATAN TEPUNG KETAN HITAM PADA BOUCHEES A LA REINE SEBAGAI DESSERT LOKAL - Prihastuti Ekawatiningsih, Yhola Kiki Nor Faridha (Prosiding Pendidikan Teknik Boga Busana, 2020)
ABSTRACT This research aims to; (1) Discovering recipe for Black Bouchees A la Reine products with the substitution of black glutinous flour, (2) Knowing people’s acceptance of Black Bouchees A la Reine by substituting the basic ingredients with black glutinous flour. (3) Determine nutritional information on Black Bouchees A la Reine products with the substitution of black glutinous flour. This research is a research that uses 4D research method, using Define, Design, Develop, and Disseminate. The steps taken in this stage are the stages of determining the product and substitution material, planning development by making products to be developed, Validation I and II by experts, limited product control tests and substitution of 30 semi-trained panelists, and testing of substitution product exhibitions with 80 panelists. Validation form is used as a measure of public acceptance of Black Bouchees A la Reine products in terms of color, aroma, texture, taste, and overall. The results showed the level of acceptance in Black Bouchees A La Rheine which had been substituted with 60% black glutinous flour was 95.93% for color, 92.81% for aroma, 95.93% for texture, 95.53% for flavor, and 95, 53% for the whole. It can be concluded that public acceptance in the last project food exhibition test shows the result was very like the product. Keywords: Black Glutinous Flour, Puff Pastry, Bouchees A La Reine